2021
DOI: 10.51985/jbumdc2019138
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Significant Variation of Paranasal Sinuses on CT-Scan

Abstract: Anatomical variations are not diseases and can be found in every individual. Due to the anatomical variations, the structural changes occur in nearby anatomical relations. By keeping in mind, the vast range of anatomical variations in nasal cavity and paranasal sinuses (PNS), every case of sinusitis must be planned carefully to avoid dreadful complications of surgical procedures. Sinus anatomical variations have been associated with the etiology of sinusitis. In this regard computed tomography (CT) imaging has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…According to Stammberger and Hawke [4], CT scan of the paranasal sinuses will offer a surgical road map of the nose and paranasal sinuses to determine the existence of substantial anatomic anomalies -which may predispose the patient to chronic or recurring acute rhinosinusitis attacks. Some anatomical variations are surgically risky and can predispose neurovascular structures associated with the paranasal sinuses, such as the optic nerve and the internal carotid artery, to a fatal injury during endoscopic sinus surgery [5]. Understanding these anatomical variances is therefore critical in designing endoscopic sinus and endoscopic skull base procedures.…”
Section: Introductionmentioning
confidence: 99%
“…According to Stammberger and Hawke [4], CT scan of the paranasal sinuses will offer a surgical road map of the nose and paranasal sinuses to determine the existence of substantial anatomic anomalies -which may predispose the patient to chronic or recurring acute rhinosinusitis attacks. Some anatomical variations are surgically risky and can predispose neurovascular structures associated with the paranasal sinuses, such as the optic nerve and the internal carotid artery, to a fatal injury during endoscopic sinus surgery [5]. Understanding these anatomical variances is therefore critical in designing endoscopic sinus and endoscopic skull base procedures.…”
Section: Introductionmentioning
confidence: 99%
“…The common anatomical variants identified in humans include Agger nasi, concha bullosa, Haller cell, Onodi cell, septal deviation, pneumatized uncinate process, and paradoxical middle turbinate. [ 7 8 ] Definition of some anatomical variants is described below: Agger nasi cells are variant of ethmoidal cells located in the anterior superior portion of the middle turbinate and can obstruct the frontal recess. Concha bullosa is the pneumatization of the middle turbinate and can obstruct drainage of osteomeatal complex.…”
Section: Introductionmentioning
confidence: 99%
“…The role of these anatomical variants in the etiopathogenesis and exacerbation of chronic rhinosinusitis is still debated. [ 9 10 ] Some studies have implicated anatomical variants in the etiopathogenesis of chronic rhinosinusitis,[ 8 11 ] whereas others have identified no statistically significant link between anatomical variants and the development of chronic rhinosinusitis. [ 12 13 ] Furthermore, studies have shown that the prevalence of these anatomical variants is not significantly higher in patients with chronic rhinosinusitis than the general population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation